The Antibacterial Effect of Qutran (wood Tar) from Olive Trees on Pathogenic Bacteria - abdulrahman alasmari; Yunus Siddiqui; Mozaffarul Islam; Mohammed Al-Ghamdi; Abdulrahman El-Elai (International Journal of Phytomedicine, 2014)
Amongst the folklore medicine in Saudi Arabia, the tar preparation which is locally known as Qutran comes from various trees and has been used for a number of ailments in humans as well as in animals. This product is commercially produced and marketed in local shops selling herbs or herbal products but the source of this product is not mentioned. Three Gram positive and two Gram negative bacteria were exposed to various concentrations of Qutran and the growth inhibition was determined by the disk and agar diffusion method and enumeration of colony forming units by micro-dilution procedure. Both the Gram positive and Gram negative microorganisms showed a great sensitivity in terms of reduction in colony forming unit counts (CFU). Disk and agar diffusion assays showed a phenomenal inhibition of bacterial growth to Gram positive but lesser inhibition of bacterial growth in Gram negative bacteria. It was observed by the enumeration of CFU counts that the Qutran exerts more growth inhibition (killing effect) on Gram positive microorganisms than onto Gram negative bacteria. This effect could be taken as action on the mucopeptide content of Gram positive bacteria than its presence in the trilaminar cell walls of Gram negative bacteria. The minimal biocidal activity (MBC) of Qutran towards the Gram positive microorganisms tested was determined as ≤0.625mg/ml, while the Gram negative microorganisms showed no growth above 1.25mg/ml.